Dinâmica populacional e evolução de dano de Triozoida limbata(Hemiptera: Psillydae) em goiabeira, em Jaboticabal, SP - Colombi, Carlos Alexandre; Galli, Julio Cesar [UNESP] (Universidade Federal de Lavras (UFLA), 2009)
The present work aimed at learning the population dynamic of Triozoida limbata (Enderlein, 1918) (Hemiptera: Psyllidae) in a guava orchard submitted to the minimum use of insecticide in Jaboticabal - SP. For the study of population fluctuation and the evolution of damage from the psillid we analyzed 20 plants of the orchard biweekly, during the period from March 2005 to June 2006. For each plant we evaluated 10 leaves containing the symptom of the attack from the psillid. The evaluated parameters were the number of nymphs and the percentage of damage caused in the leaves, in accordance with a scale of notes. These parameters were analyzed in histograms and correlated to the meteorological factors. The population density of the psillid increased considerably with the approach of the spring and presented a positive correlation with the temperature. The level of damage of the psillid accompanied the population density of the pest. According to the data found in this work we may conclude that the increase of the temperature causes an increase in the population density of T. limbata and the largest population densities from psillid occur in the months of September to November and the smallest densities occur between the months of May and July.
Population dynamic and evolution of damage of Triozoida limbata (Hem.: Psillydae) in guava orchard in Jaboticabal city, State of São Paulo
Keywords: Psillid; Population fluctuation; monitoring; Psidium guajava